EFEKTIVITAS PUPUK ORGANIK PUYUH DAN VOLUME AIR TERHADAP SIFAT-SIFAT AGRONOMI PADA TANAMAN SAWI PAKCOY (Brassica rapa) - Widata, Sri; Arnanto, Driska; Pusasi, Saipul Anwar (Fakultas Pertanian, Universitas Janabadra, 2024)
The study aimed to determine the effect of quail organic fertilizer and water volume on agronomic properties in pakcoy (Brassica rape) plants. The experiment was carried out at the Asmadewa Green House, Faculty of Agriculture, Cleban, Annual, Umbulharjo District, Yogyakarta. Research location is abaut 114 meters above sea level. This study was compiled using a Complete Randomized Design (CRD) with two factors. The first factor is the dose of quail manure (P) consisting of 3 level, 10 tons / ha (P1), 15 tons / ha (P2), 20 tons / ha (P3). The second factor is the volume of water (A) consisting of 3 level, 600 ml (40% KL) (A1), 750 ml (50% KL) (A2), 900 ml (60% KL) (A3). Volume of water irrigation was given in every 2 days for each different level. All treatment repeated by 3 times. Observation variables are : plant height, leaf length, number of leaves, leaf width, plant fresh weight, plant dry weight, stem diameter, root length, fresh weight of roots, dry weight of roots. Data was processed with Anova (Analysis of Variance) carried out advanced analysis using DMRT (Duncan's Multiple Range Test). The results showed that there was an interaction between the dose of 15 tons/ha of fertilizer and the volume of 900 ml (60% KL) of water on the number of leaves, plant fresh weight, plant dry weight, root fresh weight and root dry weight. Meanwhile, in the combination of 15 tons/ha and a volume of 600 ml (40% KL) of water, interactions occurred on plant height, leaf length, and leaf width. Whereas at a fertilizer dose of 20 tons/ha and a volume of 600 ml (40% KL) of application, there was an interaction only on the diameter of the stem, while at a volume of 750 ml (50% KL) of water there was an interaction on root length. Keywords : Mustard, Quail Fertilizer and Water Irigation, Growth Plant INTISARIPenelitian bertujuan untuk mengetahui pengaruh pupuk organik puyuh dan volume air terhadap sifat - sifat agronomi pada tanaman sawi pakcoy (Brassica rapa). Percobaan dilaksanakan di Green House Asmadewa Fakultas Pertanian, Cleban, Tahunan, Kecamatan Umbulharjo, Yogyakarta . Lokasi penelitian berada pada ketinggian 114 mdpl. Penelitian ini disusun menggunakan Rancangan Acak Lengkap (RAL) dengan dua faktor. Faktor pertama adalah dosis pupuk kandang puyuh (P) terdiri dari 3 aras yaitu: 10 ton/ha (P1), 15 ton/ha (P2), 20 ton/ha (P3). Faktor kedua adalah volume pemberian air (A) terdiri dari 3 aras yaitu: 600 ml (40% KL) (A1), 750 ml (50% KL) (A2), 900 ml (60% KL) (A3). Volume pemberian air dilakukan setiap 2 hari sekali. Diulang, sebanyak 3 kali. Variabel pengamatan meliputi tinggi tanaman, panjang daun, jumlah daun, lebar daun, berat segar tanaman, berat kering tanaman, diameter batang, panjang akar, berat segar akar, dan berat kering akar. Data diolah dengan sidik ragam Anova (Analysis of Variance) dilakukan analisis lanjutan dengan menggunakan DMRT (Duncan’s Multiple Range Test). Hasil penelitian menunjukkan adanya interaksi antara dosis pupuk 15 ton/ha dan volume pemberian air 900 ml (60% KL) terhadap jumlah daun, berat segar tanaman, berat kering tanaman, berat segar akar dan berat kering akar. Sementara pada kombinasi 15 ton/ha dan volume pemberian air 600 ml (40% KL) terjadi interaksi pada tinggi tanaman, panjang daun, lebar daun. Sedangkan pada dosis pupuk 20 ton/ha dan volume pemberian 600 ml (40% KL) terjadi interaksi hanya pada diameter batang, sementara pada volume pemberian air 750 ml (50% KL) terjadi interaksi pada panjang akar. Kata kunci : Sawi, Pupuk Puyuh dan Volume Air, Sifat Agronomi